VD_FINDINFO Jug / 2016 / 76 vom 12. November 2015 - VD Tribunal cantonal (2015)
ABUS DE CONFIANCE, ESCROQUERIE, CONCOURS D'INFRACTIONS, RÉVOCATION DU SURSIS, DÉPENS | 138 ch. 1 CP, 146 CP, 40 CP, 42 al. 2 CP, 42 al. 3 CP, 46 al. 1 CP, 46 CP, 49 al. 1 CP, 49 CP, 50 CP